Measuring user acceptance of E-Syariah System using UTAUT model / Sabiroh Md Sabri ... [et al.] - Md Sabri, Sabiroh; Wan Mohammad, Siti Hajar; Muhammad, Norrini; Idris, Asma' Rashidah (2012)
Information technology acceptance research has offered many competing models which try to understand users' acceptance of information systems. One of them is the Unified Theory of Acceptance and Use of Technology (UTAUT) which intends to predict and explain user acceptance of new IT which is eventually influenced by the users' behaviors. This study empirically measure the user acceptance of E-Syariah system implemented in the Perak Syariah Judiciary Department using the Unified Theory of Acceptance and Use of Technology (UTAUT) model. Data were collected through self-administered questionnaires which were distributed to the users of E-Syariah system in the Perak Syariah Judiciary Department. Results of this study have shown that the E-Syariah system has been highly accepted by the users in Perak Syariah Judiciary Department. The result has also contributed to the understanding of the factors that contribute to the user acceptance of the E-Syariah system. Since E-Syariah is one of the E-Government applications being implemented in Malaysia, this study should assist the organization in identifying whether the objectives of the E-Syariah implementation have been achieved or not. It should also contributes in assisting the Government to quantify the return of investment in Government's information system project and emphasize the importance of user involvement during the development of a new system especially for the Government use in the future.